2005
DOI: 10.1051/0004-6361:200500096
|View full text |Cite
|
Sign up to set email alerts
|

A simple model for the complex lag structure of microquasars

P. Varnière

Abstract: Abstract. The phase lag structure between the hard and soft X-ray photons observed in GRS 1915+105 and XTE J1550−564 has been said to be "complex" because the phase of the Quasi-Periodic Oscillation fundamental Fourier mode changes with time and because the even and odd harmonics signs behave differently. From simultaneous X-ray and radio observations this seems to be related to the presence of a jet (level of radio emission). We propose a simple idea where a partial absorption of the signal can shift the phas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…The phase lag between the hard and soft X-ray photons in GRS 1915+105 changes sign during the plateau state and produce complex behavior (Muno et al 2001). Varniere (2005) has suggested that anything located inside the inner radius of the accretion disk (in our case wind) that can absorb a small part of soft X-ray flux can explain the changing of sign of the lag and its complex behavior during the plateau state. Other consequences of our results is that one would not expect oscillations/ baby jet type of IR & radio emission in Cyg X-3 (not observed so far (Dhawan, Mirabel, & Rodriguez 2000)) as has been observed in GRS 1915+105 (Mirabel et al 1998;Eikenberry et al 1998;Ishwara-Chandra, Yadav, & Pramesh Rao 2002).…”
Section: Resultsmentioning
confidence: 91%
“…The phase lag between the hard and soft X-ray photons in GRS 1915+105 changes sign during the plateau state and produce complex behavior (Muno et al 2001). Varniere (2005) has suggested that anything located inside the inner radius of the accretion disk (in our case wind) that can absorb a small part of soft X-ray flux can explain the changing of sign of the lag and its complex behavior during the plateau state. Other consequences of our results is that one would not expect oscillations/ baby jet type of IR & radio emission in Cyg X-3 (not observed so far (Dhawan, Mirabel, & Rodriguez 2000)) as has been observed in GRS 1915+105 (Mirabel et al 1998;Eikenberry et al 1998;Ishwara-Chandra, Yadav, & Pramesh Rao 2002).…”
Section: Resultsmentioning
confidence: 91%
“…The INTEGRAL data were retrieved from the public archive and correspond to the Target of Opportunity (TOO) observations performed between January 5, 2005 andFebruary 21, 2005 (MJD 53376.27-53422.05 …”
Section: Observations and Data Analysismentioning
confidence: 99%
“…While models based on Comptonisation of low-energy photons in a non-uniform corona can reproduce the amplitude and energy dependence of the hard lags the change in sign of the lags are hard to explain by invoking light-travel time differences between photons at different energies (but see Ohkawa et al 2005). Recently, Varnière (2005) has proposed that partial absorption (related to the jet mechanism) of the signal can account for the phase lag reversal in microquasars. Since X-ray pulsars do not show radio jets, other mechanisms producing the absorption of the soft/low-energy X-rays must be at work if the phase lag behaviour of V0332+53 is to be explained with this model.…”
Section: Phase Lagsmentioning
confidence: 99%
“…Psaltis et al,1999). Here we focus on a basic paradigm for the modulation and leave explanations of possible harmonic relations and phase lag behavior Varnière (2005) for further work. Black hole microquasars avoid the role of any solid stellar surface, and offer a purer probe of the accretion process without interaction with a stellar surface.…”
Section: Introductionmentioning
confidence: 99%